Optimalisasi Pengelolaan Zakat untuk Pemberdayaan Masyarakat Miskin pada Amil Zakat di Kabupaten Bojonegoro - Nadya Septiana; Erly Juliyani (Al-Muzdahir : Jurnal Ekonomi Syariah, 2022)
Islam is a religion that was sent down by Allah SWT to the Prophet Muhammad SAW who became Rahmatan lil'Alamin (Grace to all nature). Islam clearly frees itself from things that are ribawi. In Islamic economic principles there are several economic instruments to help social interests such as the use of zakat, infaq, and alms funds to finance the welfare of the people. This study aims to answer, describe and analyze the formulation of the problem: 1. What is the strategy to optimize zakat management at Baznas Bojonegoro?, 2. What programs are carried out by Baznas Bojonegoro in increasing the empowerment of the poor in Bojonegoro Regency?3. Obstacles experienced by Baznas Bojonegoro in managing zakat funds and how to handle them? The type of research in this thesis includes field research. The method used in this study is to use qualitative research methods. The results of this study are 1. The strategy carried out by BAZNAS Bojonegoro, namely by conducting outreach to the people of Bojonegoro district and ASN, PNS, BUMN, BUMD as well as various agencies, institutions and mosques is used to introduce the importance of zakat and establish UPZ (Collection Unit zakat). 2. Programs run by Baznas Bojonegoro include: Religious Bojonegoro, Genius Bojonegoro, Energetic Bojonegoro, Philanthropic Bojonegoro, and Productive Bojonegoro. And it has been going very well, and almost every day Bojongoro Baznas is active in collection and distribution. 3. Obstacles experienced by BAZNAS in managing zakat in Bojonegoro Regency, namely the lack of awareness of the importance of issuing zakat.